Refugee parents' experiences of coming to Sweden: A qualitative study. (November 2022) - Västhagen, Maja; Özdemir, Metin; Ghaderi, Ata; Kimber, Birgitta; Giles, Clover Jack; Bayram Özdemir, Sevgi; Oppedal, Brit; Enebrink, Pia
Abstract: Each year, millions of people worldwide are forced to leave their homes. Many of those affected are families. There are already a considerable number of initiatives designed to support refugees who are resettling in new countries and cultures. However, few are promotive interventions aiming to support parents and thereby their children through the extraordinary challenges they face. To develop a culturally adaptive intervention, more knowledge about how refugee parents from different countries perceive and handle these challenges is needed. This study explores refugee parents' own perspectives on the obstacles, challenges and opportunities they faced during their first years in Sweden to guide the future development of promotive interventions for refugee parents. Interviews were conducted with Arabic, Kurdish, and Somali-speaking refugee parents ( n = 28; 19 mothers, 9 fathers). The interviews were examined using content analysis. One overarching theme emerged; "The new language is the key for entering social networks and society, and for helping your child in a new country". The new language was viewed as a key to integration, and to mastering parenthood in the new context. This theme consisted of four categories; "parents' motivation and hope as driving forces, " "navigating among past and present culture and values", "loneliness as a risk factor" and "a new way of being a parent and relating to an acculturation gap". These findings may help guide the development of parenting interventions for refugees, to promote integration and well-being among parents and their children.